“Internationalisation practices: a case of a highly specialised German SME” - Obolenski, Anna (2014)
Internationalisation is a highly complicated process. It has been studied for decades. However, nowadays not only multinational enterprises (MNEs) but also small and medium-sized enterprises (SMEs) are undertaking this process. Their experience has not yet been studied in detail. As SMEs are highly individual and do not follow any particular theory, this research looks at how they actually undertake internationalisation. The practice approach can be extremely helpful in analysing the internationalisation process of SMEs in order to understand how it works, and where there is space for improvement. This is because the practice method analyses what firms actually do on a routine basis that leads to internationalisation.